MEKANISME PENGAMBILAN KEPUTUSAN KEPALA SEKOLAH: ANALISIS KONSEPTUAL, DIMENSI DAN TAHAPAN SISTEMATIS - Sahrul, Sahrul; Asmawati Jafar; Anzar, Anzar; Mardiah Hasan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Global challenges and technological disruption demand a transformation in the educational sector, where school quality heavily relies on the effectiveness of principal leadership. This study aims to fundamentally examine the decision-making mechanism of school principals, focusing on three main aspects: the core concept of the principal as a decision-maker, the spectrum of roles in policy-making, and the systematic stages of the decision-making process along with its influencing factors. The research method employed is a literature review (library research) analyzing 20 reputable scientific references (international and Sinta-indexed national journals) from the past ten years. The results indicate that the principal is no longer merely an administrative officer, but a chief executive executing rational cognitive processes based on managerial authority and administrative functions. The principal's decision-making role is reflected through the EMASLIM dimensions (Educator, Manager, Administrator, Supervisor, Leader, Innovator, and Motivator). Decision effectiveness in schools operates through a structured six-stage cycle that strictly integrates three core pillars: data-driven, ethically grounded, and participatory. The synergy between tactical firmness in emergencies and community collaboration in routine policies is proven to foster a positive school climate and continuously accelerate educational quality.